Perancangan Aplikasi Kelayakan Angkutan Umum Berdasarkan Uji Kir Pada Dinas Perhubungan Kota Medan Berdasarkan Jenis Angkutan Berbasis Web Menggunakan Metode Topsis - Fahreza, Muhammad Fadli; Suriati, Suriati; Syahputri, Nenna Irsa (Universitas Islam Negeri Sumatera Utara, 2022)
The feasibility of public transportation must be carried out by the Department of Transportation to conduct tests on motorized vehicles and issue permits for proper operation, so as to minimize accidents due to motorized vehicles that are not feasible to operate but are still operating. The KIR test is a check on the vehicle, and on the Department of Transportation. KIR is a series of activities to test and inspect parts of motorized vehicles such as trucks, pickups, public transportation, buses and special vehicles in order to fulfill technical and roadworthy requirements. To test the feasibility of public transportation, the researchers made a public transportation feasibility application based on the KIR Test at the Medan City Transportation Service based on the type of web-based transportation. The design of this application was built using the TOPSIS (Technique For Others Reference by Similarity to Ideal Solution) method. The steps used in the TOPSIS method are the normalization matrix calculation process, the weighted normalization matrix calculation process, the process of determining the positive ideal solution and the negative ideal solution, the process of calculating the distance between each alternative to the ideal solution, and the process of calculating the preference value of each alternative. The application is designed using Dreamweaver cs 6 and appserv as the database. The result of the calculation process of the TOPSIS method is in the form of information on the feasibility of public transportation according to the specified conditions. The results obtained in this study is an information vehicle KIR test using the TOPSIS method which can be used to assist the Department of Transportation in testing the feasibility of public transportation. Based on the results of this study, it can be concluded that the application of determining the feasibility of the KIR test is proven to be quite helpful for certain parties in facilitating the KIR test. Keywords: KIR, TOPSIS, Public Transportation, Department of Transportation